Autism and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The prevalence and clinical manifestations of epilepsy in 302 autistic and 237 dysphasic, non-autistic children were studied at the Departments of Neurology and Pediatrics, Albert Einstein College of Medicine and Montefiore Medical Center, Bronx, New York.